Pendidikan Islam Transformatif untuk Ekonomi Sirkular: Studi Kasus Pengelolaan Sampah Berbasis Pirolisis di Pedesaan Pasuruan, Indonesia - Sofiyulloh; Enik Sulistyowati (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Purpose: This study aims to explain the process of transformative Islamic education in community-based plastic waste management through a combination of pyrolysis technology and biomass in Manikrejo Village, Pasuruan Regency, and to analyze its impact on changing paradigms, community independence, and the creation of circular economic value.Design/methodology/approach: This research employs a qualitative case study approach with data collection through participant observation, in-depth interviews with 35 informants consisting of religious leaders, village officials, waste management group administrators, training participants, and sub-district government representatives, as well as documentation during the community service program from June to December 2025. Data analysis uses an interactive model and triangulation to ensure validity.Findings: The results reveal three main stages in transformative Islamic education through this program. First, internalization of Islamic values such as cleanliness, moral responsibility, and mutual cooperation becomes the motivational foundation driving community participation, with religious figures acting as catalysts for behavioral change. Second, the implementation of learning-by-doing methods with tiered mentorship successfully transforms residents from passive recipients into competent technology operators, with 90% of participants able to operate pyrolysis reactors independently. Third, a fundamental paradigm shift occurs where plastic waste is no longer viewed as an